Validation of the tobacco, alcohol, prescription medication, and other substance use (TAPS) tool with the WHO alcohol, smoking, and substance Involvement screening test (ASSIST). (March 2022) - Carter, Gentry; Yu, Ziji; Aryana Bryan, M.; Brown, Jennifer L.; Winhusen, T.; Cochran, Gerald
Highlights: The TAPS tool is an attractive screening tool in pharmacy settings and can be integrated into existing workflows. The TAPS tool has good to excellent validity for tobacco, alcohol, and marijuana use identification. The TAPS tool had fair validity for stimulant and heroin drug use identification. Future research should work to improve the TAPS for prescription opioid, sedative, and prescription stimulant identification. Abstract: Introduction: Community pharmacies are emerging as a valuable setting to identify patients with substance use. Few tools have been specially validated to screen patients in these settings, particularly among those prescribed opioid medications. The goal of this study was to validate the performance of the Tobacco, Alcohol, Prescription medication, and other Substance use (TAPS) tool in community pharmacy settings compared to a reference-standard substance use assessment. Methods: Participants were recruited while receiving opioid medications (not solely buprenorphine) from 19 pharmacies from a large national chain in Ohio and Indiana. Adults who were not involved in the criminal justice system or receiving cancer treatment were invited to participate in a one-time, cross-sectional, self-administered, health survey which included the TAPS tool. Substance use risks calculated from the TAPS tool were compared with the reference standard, World Health Organization Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST) using confusion matrices. We calculated Areas Under the Curve (AUC) of Receiver Operating Characteristics Curves (ROC) to evaluate the TAPS tool's validity. Results: The TAPS tool showed fair or better discrimination between moderate-risk use and high-risk use for tobacco, alcohol, and prescription opioids (AUCs: 0.75–0.97 and fair or better discrimination between low-risk and moderate-risk use in five of eight subscales, including tobacco, alcohol, marijuana, stimulants, and heroin (AUCs: 0.70–0.92). Conclusion: The TAPS tool detected clinically relevant problem substance use in several drug classes and likely would be a valuable assessment for screening illicit drug use among community pharmacy patients prescribed opioid medications.